2021
DOI: 10.1080/10833196.2021.1876598
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing active transport as a planetary health intervention – benefits, challenges and recommendations

Abstract: A high proportion of people are insufficiently physically active. The reasons for this are complex and in part relate to social determinants of health, lifestyle choices, and deleterious environmental conditions like climate change, loss of green and outdoor environments and a concomitant loss of biodiversity. Physiotherapists, and other health professionals, may have a positive impact on these global issues, through the encouragement of active transport, and advocacy to reduce barriers to its uptake and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…specifically the connection between physiotherapy and planetary health, physiotherapists can implement environmentally sustainable physiotherapy practices (Maric et al, 2022;Padhy, 2021). Physiotherapists can also promote using active transport with their patients, which could contribute to planetary health as well as human health by increasing physical activity (Stanhope et al, 2021;Toner et al, 2021). While the current research identified some barriers for…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…specifically the connection between physiotherapy and planetary health, physiotherapists can implement environmentally sustainable physiotherapy practices (Maric et al, 2022;Padhy, 2021). Physiotherapists can also promote using active transport with their patients, which could contribute to planetary health as well as human health by increasing physical activity (Stanhope et al, 2021;Toner et al, 2021). While the current research identified some barriers for…”
Section: Discussionmentioning
confidence: 82%
“…As health professionals, physiotherapists also have a role in mitigating climate change and its adverse effects on health through personal action, education, advocacy, and health promotion (Maric & Nicholls, 2019). There is a growing body of literature discussing how physiotherapists can fulfil this role (Foo, 2016; Jones, 2009; Maric & Nicholls, 2019; Maric et al., 2022; Myers, 2017; Stanhope et al., 2021; Toner et al., 2021). For instance, encouraging the use of active transport, such as walking or cycling, which not only increases physical activity, but also reduces greenhouse gas emissions and air pollution (Christe, 2021; Padhy, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, active transport to university should be promoted by ensuring safe infrastructure, providing rental bicycles and e-bikes, and linking with sustainable public transport [ 31 ]. The Bicycle Friendly University program awards U.S. higher education facilities that provide physical infrastructure, education programs, encouragement, incentives, and equitable laws to promote biking [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable potential also exists for improving planetary health through these environmental approaches [21][22][23]. The transport sector plays a significant role in greenhouse gas emissions [22], and urban design that prioritizes motorized transport can contribute to the urban heat island effect [80].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous co-benefits exist when environments are designed to enable children's physical activity, including supporting planetary health (e.g., through reducing air pollution via shifting from motorized to active travel modes [20][21][22]). Indeed, encouraging active travel has been suggested as a "planetary health intervention" recognizing the multiple pathways through which human travel behaviors and planetary health are linked [23]. Children's physical activity tracks over the lifespan [24,25], so establishing healthy physical activity habits, including active travel, early in life can have a long-standing impact on both human and planetary health.…”
Section: Introductionmentioning
confidence: 99%